STUDY ON THE STRUCTURAL CHARACTERISTICS OF LARGE WIND TURBINE COMPOSITE BLADE BASED ON BEND-TWIST COUPLING - ZHANG Li; MIAO WeiPao; LI Chun; YAN YangTian; LIU QingSong; WANG Bo (Jixie qiangdu)
In order to study the structural characteristics of different types of bend-twist coupling blades, the NREL 5 MW wind turbine blade was used as the research object, combined with composite material laying design to establish finite element models of different BTC blades, the aerodynamic load of the blades were solved by CFD method. The modal, strength and buckling of the blades were calculated and the effects of different coupling regions and coupling angles on the structural characteristics of the blades were analyzed. The results show that the natural frequencies of BTC blades are mostly lower than that of the traditional blades. The skin-coupled blades have the smallest change and the fully coupled blades have the greatest influence; the BTC blades can reduce the internal von Mises stress and strain peak value and improve the fatigue life of the blade. The skin-coupled blades have the largest reduction and the spar cap-coupled blades have the smallest reduction. The skin-coupled blades have the best load reduction effect when θ=20°; the shear stress of the BTC blades are mostly higher than that of the traditional blades, only the maximum shear stress of the skin-coupled blades θ=20° is lower than that of traditional blades; the bend-twist coupling characteristics of the blades have a certain impact on its stability. The critical buckling load of spar cap-coupled blades have a large decrease, while other BTC blades have a slight increase, and the amount of the first-order buckling deformation is lower than traditional blades.